2020
DOI: 10.1093/bib/bbaa311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and immunogenomic landscape analyses of the immune cell signature based prognostic model for patients with breast cancer

Abstract: Breast cancer is one of the most common types of cancers and the leading cause of death from malignancy among women worldwide. Tumor-infiltrating lymphocytes are a source of important prognostic biomarkers for breast cancer patients. In this study, based on the tumor-infiltrating lymphocytes in the tumor immune microenvironment, a risk score prognostic model was developed in the training cohort for risk stratification and prognosis prediction in breast cancer patients. The prognostic value of this risk score p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 60 publications
4
65
0
Order By: Relevance
“…We also evaluated transcriptome sequencing data and found that the cellular proportion-based on our prognostic model can well predict the prognosis of TCGA-BRCA cohorts, and confirming the previous studies (Figure 3B) (16,52). Since the accuracy of deconvolution is affected by many factors (such as data type (microarray/RNA-seq)), we attempted to find stable signatures for predicting the prognosis of BC patients.…”
Section: Discussionsupporting
confidence: 83%
“…We also evaluated transcriptome sequencing data and found that the cellular proportion-based on our prognostic model can well predict the prognosis of TCGA-BRCA cohorts, and confirming the previous studies (Figure 3B) (16,52). Since the accuracy of deconvolution is affected by many factors (such as data type (microarray/RNA-seq)), we attempted to find stable signatures for predicting the prognosis of BC patients.…”
Section: Discussionsupporting
confidence: 83%
“…immunopredictive score (IMPRES) model for melanoma, 35 a neoantigen fitness model for melanoma and lung cancer, 36 and the immune-related risk score model for breast cancer. 37 However, the choice of effective prediction markers for GC immunotherapy is limited. Based on the DEGs between hot and cold tumors, we constructed a clinical prediction model related to immune infiltration, and to predict the OS of patients receiving immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a comprehensive collection of marker genes marked to 184 ICSs was referred from a literature ( Wang S. et al, 2020 ), in which these ICSs and the corresponding marker genes were collected from diverse resources, including previous studies and database. To be specific, 25 signatures were collected from Bindea et al (2013) , 68 signatures were collected from the study of Wolf et al (2014) , 17 signatures were downloaded from the ImmPort database ( Bhattacharya et al, 2014 ), 24 cell signatures were collected from the study of Miao et al (2020) , and 22, 10, and 10 signatures were collected from CIBERSORT ( Newman et al, 2015 ), MCPcounter ( Becht et al, 2016 ; R package, version 1.2.0) and imsig ( Nirmal et al, 2018 ; Rpackage, version 1.1.3), respectively.…”
Section: Methodsmentioning
confidence: 99%